EDIBLE OIL USE PRACTICES AMONG FOOD VENDORS IN OWERRI METROPOLIS, IMO STATE, NIGERIA - Nzubechukwu Kanu, Michelle; Nwabuaku Kanu, Winifred (African Journal of Social and Behavioural Sciences, 2024)
The quality of edible oils used in street food preparation is of paramount importance for both public health and culinary excellence. The repetitive use of edible oils in the preparation of street foods, particularly fried items, raises significant public health concerns in places around the world. This study aims to investigate the factors that influence edible oil practices among street fried food vendors in Owerri Metropolis Imo State, Nigeria, to address a critical knowledge gap that hampers efforts to enhance food safety. A cross-sectional study design was employed, using quantitative surveys to gather data. The study sampled 200 street fried food vendors using convenience and purposive sampling techniques. Data collection focused on, the socio-demographic characteristics of vendors, level of compliance with safety standards and factors that limit the adoption of recommended safety practices, among others. Descriptive analysis (percentage and frequency) was used to analyse the data. Findings revealed low compliance with safety standards among street fried food vendors in Owerri Metropolis. Limited financial resources/ Cost of quality oil (economic factors) were the primary drivers of unsafe practices. Vendors made use of cheap oil, with many reusing oil multiple times due to financial constraints. The study recommends creating awareness of cost- effective oil management strategies, enhancing regulatory measures and educational initiatives to improve food safety among fried food street food vendors in the area. This approach is crucial for safeguarding consumer health and promoting sustainable street food vendor practices.